Pemberdayaan Santri Ma’had Al-Jami’ah Tulungagung melalui Pelatihan dan Pendampingan Diversifikasi Produk Berbahan Dasar Murbei - Setyowati, Eni; Musrikah, Musrikah (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Santri at Ma'had Al-Jami'ah Tulungagung are students who receive bidik misi scholarships who come from poor economic backgrounds, but have high intelligence and enthusiasm. They need to develop entrepreneurial skills. Large but underutilized land is an asset that needs to be developed. In fact, human resources and available land assets have not been maximized. In the Tulungagung area there are many wild mulberry plants that have high health benefits, which need to be cultivated and utilized. The objectives of this community service are: (1) to conduct training and mentoring on mulberry cultivation, (2) to conduct training and mentoring on mulberry-based product processing, and (3) to conduct training and mentoring on creative marketing strategies. The method used is ABCD (Asset-Based Community Development), which consists of discovering, dreaming, designing, defining, doing, and monitoring evaluation. The results of the community service showed that: (1) the students can cultivate mulberry well, (2) the students can make mulberry tea and syrup products, and (3) the students can learn and apply creative marketing, which is useful for increasing income and entrepreneurship.